Spatiotemporal Variance Image Reconstruction for Thermographic Inspections - Logan M. Wilcox; Emily M. Johnson; Emma T. Bohannon; Catherine E. Johnson; Kristen M. Donnell (IEEE Open Journal of Instrumentation and Measurement)
Active microwave thermography (AMT) is a nondestructive testing and evaluation (NDT&E) technique that utilizes a radiating antenna to induce a thermal increase on or within a specimen under test (SUT). The radiated power density is spatially nonuniform and therefore results in a spatially nonuniform thermal excitation, which may result in missed or false indications of defects. To this end, this work proposes a novel image reconstruction technique for nonuniform excitation/heating and is referred to as spatiotemporal variance reconstruction (STVR). STVR utilizes the spatial and temporal variance of the surface thermal profile. STVR is advantageous in that it does not require a reference measurement nor manipulation of the interrogating signal to mitigate the effect of the nonuniform thermal excitation. To illustrate the improvements offered by STVR, AMT measurements were completed on a set of carbon fiber-reinforced polymer (CFRP) structures with an absorbing topcoat. Additional thermographic measurements were completed utilizing a halogen lamp source on a pressed high explosive (HE) SUT. In all cases, the STVR-processed results provide an indication of the defect, within 5% spatial error, without the need for a reference measurement or signal manipulation, which was not previously possible.